An Evaluation of the Intensive Care Unit Resources and Utilization in Two Governmental Hospitals in Tripoli, Libya - Atia, Ahmed; Ashur, Abdulsalam; Elmahmoudi, Hosam; Abired, Ahmed; Bkhait, Nafisa (Al-Mukhtar Journal of Sciences, 2019)
The growing population in Tripoli is projected to have a sustained increase in the demand for health services, especially in-service areas with limited resources such as intensive care units (ICUs). Currently, ICUs in the city of Tripoli routinely operate at or near full capacity and have a limited ability to accommodate the next critically ill patient. This disparity in demand and supply makes a substantial strain on our health care system. In response to this rising problem, the current study aimed to investigate the ICU capacity in the two largest hospitals in Tripoli, Libya. This is a retrospective observational study that conducted to compare ICU capacities and admission in the Medical intensive care unit (MICU) and surgical intensive care unit (SICU) of Tripoli Medical center (TMC) and Alkhadra hospital (AH) in Tripoli city of Libya. ICUs capacity and admissions were assessed and recorded in data collection sheet that includes; type of ICU, number of available ICU beds, number of available functional monitors, number of available functional mechanical ventilators, number of patients admitted to the ICU, and number of ICU nurse. In TMC, MICU occupied with 4 beds, 4 monitors, 3 mechanical ventilators (MV), 5 patients admitted, and 13 nurses. Whereas SICU engaged with 4 beds, 5 monitors, 5 MV, 13 patients admitted and 15 nurses. While MICU at AHT was occupied with 4 beds, 4 monitors, 1 MV, and 4 admitted patients with 1 nurse care, SICU at CHT was comprised of 3 beds, 3 monitors, 0 MV, and 3 patients with 1 nurse stuff. We concluded that facilities at both MICU and SICU at Alkhadra hospital of Tripoli were less efficient than MICU and SICU at Tripoli Medical centre. Both ICUs at AHT had not enough beds, observation equipment, and nursing staff to take care of patients. However, facilities of both ICUs at TMC were also not sufficient.